Edukasi Kesehatan Fisik dan Mental Bagi Lansia - Dhina Ayu Susanti (Jurnal SADEWA, 2026)
The aging process is a biological thing that everyone will definitely experience. The aging process in the elderly is influenced by several external factors such as environmental factors, lifestyles, especially eating patterns, and social factors. A good diet while young will affect health when entering the elderly. However, the fact is that the older a person gets, the more often they neglect a good diet and lifestyle so that it will affect the physical and mental health of the elderly. Elderly people with a good diet and can manage stress in their lives will have a positive impact on their quality of life. Therefore, education about physical and mental health is needed for the elderly so that the elderly have a good quality of life in their old age. The purpose of this community service is to provide motivation to the elderly so that they can maintain their quality of life. The activity method uses interactive lectures and discussions with the target being 23 participants who are students. Through community service activities, participants gain additional knowledge about how to improve their health in old age so they can improve their quality of life